Probability of Cardiovascular Death in Patients with Prostate Cancer Receiving Androgen Deprivation Therapy (ADT): A Comprehensive Analysis - Amira Fithri Rofifa; Adhananta Zhafran Prawira; Muhammad Zulfan Rifqiawan; Dinda Eka Permatasari; Besut Daryanto; Kurnia Penta Seputra (Brawijaya Journal of Urology, 2024)
Background. ADT, or androgen deprivation therapy, is one of the most effective treatments for prostate cancer. It works by reducing testosterone levels to levels that would cause castration either medication or surgery. ADT has been associated with a significant improvement in cancer-related survival; however, reports of cardiovascular (CV) problems connected to ADT treatment are on the rise.Objectives. To demonstrate the risk of cardiovascular death in patients with prostate cancer treated with ADT.Methods. This study demonstrated compliance with the parameters set forth by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. With this search strategy, articles published between 2014 and 2024 were taken into consideration. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, SagePub, and Google Scholar. Review articles, previously published works, and partially completed works were all selected not to be considered.Results. We found 221 papers in the PubMed database, 47 articles on SagePub, and 9050 items on Google Scholar as a result of our search. 7287 records were removed before screening, hence 2030 articles were received for review. Following a record-exclusion screening, we assembled ten publications in total. Five studies that fulfilled the requirements were included.Conclusion. ADT is frequently a crucial component of the treatment of prostate cancer; patients should also receive counselling regarding their elevated risk of cardiovascular events and should think about taking preventative measures to lower that risk.